IMPLEMENTASI SENTRA STEAM DAN CODING PADA ANAK USIA DINI (PENELITIAN KUALITATIF DI KB-TK LABSCHOOL UNJ JAKARTA PADA TK B) - Adlia Izmatu arham; Isti Rusdiyani; Kristiana Maryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the readiness of Labschool in creating the nation's children who are literate in technology and critical understanding as well as problem solving through the children's learning process to stimulate problem solving needed in the modern era now in the last 2 years. The teacher's duties are needed in the process of planning, implementing, evaluating and solving problems from obstacles and support for learning at Labschool Kindergarten, not only the teacher is also a facilitator, a child safety guard, ensuring that every child is safe, comfortable and independent. The sustainability of all of this cannot be separated from internal cooperation, namely the school and external, namely parents of students, and the environment, with the aim of facilitating all children's learning activities both in terms of morals and morals. The teacher also ensures that every process that the child does is in accordance with the development through documentation, as well as recording the process of achieving the development that the child does, the purpose of this research is to describe how the process of STEAM and coding center activities is carried out starting from planning, implementation, evaluation and knowing the obstacles and support that KB-TK Labschool gets. Overall, the STEAM and coding centers carried out by Labschool Kindergarten are running according to plan and quickly follow up on all evaluations for better in the future.